Information support for strategic management decisions based on total life cycle costing of the product - G. A. Adamova (Управление)
The development of innovative technologies in production against the background of the globalization of commodity markets and increased competition has led to a reduction in the life cycle of most products of industrial companies, while increasing the requirements for the validity of management decisions regarding the release of new types of products and product range planning. The purpose of this research is to study the problem of information support for the strategic management of large manufacturing companies in the context of the need to make effective management decisions on the planning of the product range, the implementation of capital investment, the launch of new products based on the implementation and use of the full life cycle calculation system. The paper analyses the prerequisites for the emergence of a system of calculating the full life cycle of a product, considers the key features and advantages of using this system. The study formulates the requirements for the organization of cost accounting in the context of the application of the calculation of the full life cycle, gives recommendations for planning and controlling costs in the context of the stages of the “life” of the product. The author made a conclusion about the expediency of implementing the system under consideration for Russian manufacturing companies, revealed the sequence of applying the calculation method in the conditions of its use. The article shows the possibilities of using Japanese cost management systems and cost calculation in relation to individual stages of the life cycle. The paper gives the characteristic features of companies for which the use of this system is most appropriate.